Mitochondrial myopathy: a genetic study of 71 cases. Issue 8 (August 1988) - Harding, A E; Petty, R K; Morgan-Hughes, J A
Abstract : Of 71 index cases with histologically defined mitochondrial myopathy, 13 (18%) had relatives who were definitely affected with a similar disorder. Eight familial cases from four families were confined to a single generation. In five families maternal transmission to offspring occurred. There were no instances of paternal transmission, but one patient had an affected cousin in the paternal line. No consistent clinical syndrome or pattern of inheritance emerged for any identified defect of the mitochondrial respiratory chain, localised biochemically in 41 cases. Overall, the recurrence rate was 3% for sibs and 5.5% for offspring of index cases. Review of published reports of familial cases of mitochondrial myopathy suggests that the ratio of maternal to paternal transmission is about 9:1. We conclude that these disorders may be caused by mutations of either nuclear or mitochondrial genes.